Some nematodes and acanthocephalans from exotic ornamental freshwater fishes imported into Germany - Moravec, F; Wolter, J; Körting, W (Folia parasitologica, 1999)
Five species of adult nematodes, unidentifiable nematode larvae, and three species of acanthocephalans, were found in freshwater ornamental fishes newly imported into Germany from Brazil, Colombia, Indonesia, Malaysia, Nigeria, Peru, Sri Lanka and Thailand. The following species were identified: Adult Nematoda: Pseudocapillaria tomentosa, Capillariidae gen. sp., Dichelyne hartwichi sp. n., Procamallanus (Spirocamallanus) pintoi and Spinitectus allaeri; Acanthocephala: Pseudogorgorhynchus arii gen. et sp. n., Neoechinorhynchus sp. and Pallisentis sp. The nematode Dichelyne hartwichi sp. n. (male only) from the intestine of Chelonodon fluviatilis (Hamilton) from Thailand is characterised mainly by the presence of minute cuticular spines on the tail tip, length of spicules (510 microns) and arrangement of caudal papillae. The acanthocephalan Pseudogorgorhynchus arii sp. n. from the intestine of Ariopsis seemanni (Günther) from Colombia represents a new genus Pseudogorgorhynchus gen. n., differing from other genera of the Rhadinorhynchidae mainly in possessing a small proboscis armed with markedly few (18) hooks arranged in six spiral rows. Spinitectus macheirus Boomker et Puylaert, 1994 and Spinitectus moraveci Boomker et Puylaert, 1994 are considered junior synonyms of Spinitectus allaeri Campana-Rouget, 1961.
Keywords: Nematode Infections; tropické klima; Acanthocephala; mužské pohlaví; Helminthiasis, Animal; Německo; helmintózy zvířat; nematodózy; Nematoda; ženské pohlaví; zvířata; nemoci ryb; Germany; Tropical Climate; hlístice; Fish Diseases; Fishes; ryby; Female; Male; Animals